Ecotourism: Bibliometric Analysis in 2023 - Dhia, Ahmad Naisaburi Bintang; Sirait, Rosaulina Dwi Putri; Kusumaningrum, Anisa Putri; Pradini, Gagih; Agustiani, Fitri (CV ODIS, 2023)
Tourism has many types, one of which is ecotourism which has been widely applied, but there are still few that provide a global picture of the concept. The purpose of this study is to identify ecotourism-based tourism trends as well as other scientific products over time, such as source, author, and type of document. Bibliometric analysis was used to analyze a sample of 194 articles from Google Scholar published in 2023. Ecotourism is the main keyword used in article titles, abstracts, and keywords to get metadata retrieved from the Google Scholar bibliographic database, on Monday, October 2, 2023. The tools used in bibliometric analysis are Microsoft Excel which is used to perform frequency analysis, VoS viewer for data visualization, and Harzing's Publish or Perish used for citation and analysis metrics. This study's results show that most related articles are published in scientific journals, compared to others. Related articles published in scientific journals have obtained the highest citations compared to others